Revision Reverse Total Shoulder Arthroplasty With Pectoralis Major Transfer for Anterior Deltoid Deficiency: A Case Report. Issue 2 (27th April 2022) - Wheelwright, John C.; Featherall, Joseph; Kazmers, Nikolas H.; Tashjian, Robert Z.; Chalmers, Peter N.
Abstract : Case: A 70-year-old male patient presented with anterior deltoid weakness from Parsonage-Turner neuropathy status post failed nerve transfer and a failed total shoulder arthroplasty with pseudoparalysis. The patient underwent revision to a reverse total shoulder arthroplasty with concomitant pectoralis major transfer to substitute for the anterior deltoid. An excellent functional result was attained as early as 6 weeks after surgery. Conclusion: Pectoralis major transfer can be an effective treatment option for isolated anterior deltoid insufficiency, even in the setting of a reverse total shoulder arthroplasty.